Low-income public housing and neighbourhood planning and development in the city of Tehran, Iran - 359246 Khavidi, Rahim (Ann Arbor, Mich. : UMI, 1978)
Thesis (Ph.D.) - University of Wisconsin, Milwaukee, 1978